Street law : - Arbetman, Lee P. (West Publishing Company, 1994)
Gaining a practical understanding of the law and the legal system. Street Law: A Course in Practical Law's interactive methods focus on legal issues relevant to your students' lives that help them develop the knowledge and skills essential to living in our law-related society.